Potentialities of steady-state and transient thermography in breast tumour depth detection: A numerical study. Issue 123 (January 2016) - Amri, Amina; Pulko, Susan Helen; Wilkinson, Anthony James
Highlights: Steady state thermal contrast magnitude depends on the tumour diameter and depth as well as on the breast density. The Full Width at Half Maximum calculated at the surface of the breast enlarges as the tumour depth increases but also depends on the tumour diameter. Transient thermal contrast trends present three important characteristics including the response time, the transient peak and its corresponding observation time. The observation time is likely a potential time for tumour depth detection as it does not strongly depend on the tumour diameter or on the chilling temperature and its duration. Abstract: Breast thermography still has inherent limitations that prevent it from being fully accepted as a breast screening modality in medicine. The main challenges of breast thermography are to reduce false positive results and to increase the sensitivity of a thermogram. Further, it is still difficult to obtain information about tumour parameters such as metabolic heat, tumour depth and diameter from a thermogram. However, infrared technology and image processing have advanced significantly and recent clinical studies have shown increased sensitivity of thermography in cancer diagnosis. The aim of this paper is to study numerically the possibilities of extracting information about the tumour depth from steady state thermography and transient thermography after cold stress with no need to use any specific inversion technique. Both methods are based on the numerical solution of Pennes bioheat equation for a simple three-dimensional breast model. The effectiveness of two approaches used for depth detection from steady state thermography is assessed. The effect of breast density on the steady state thermal contrast has also been studied. The use of a cold stress test and the recording of transient contrasts during rewarming were found to be potentially suitable for tumour depth detection during the rewarming process. Sensitivity to parameters such as cold stress temperature and cooling time is investigated using the numerical model and simulation results reveal two prominent depth-related characteristic times which do not strongly depend on the temperature of the cold stress or on the cooling period.